A Systematic Review of Antibiotic Administration Incidents Involving Neuraxial Routes: Clinical Analysis, Contributing Factors and Prevention Approaches - Santosh Patel (Pain and Therapy)
Abstract Introduction This review aimed to investigate the inadvertent administration of antibiotics via epidural and intrathecal routes. The secondary objective was to identify the contributing human and systemic factors. Methods PubMed, Scopus and Google Scholar databases were searched for the last five decades (1973–2023). The author recorded the antibiotics involved, the route of administration, clinical details and consequences in a standardised format. The author utilized the Human Factors Analysis Classification System (HFACS) framework to identify contributing factors. Results Twenty publications reported neuraxial administration of antibiotics (adults, 19, paediatric, three patients). Fifteen (of 22) incidents happened in the post-surgical or post-chronic pain procedure period. Most errors (14 of 22) occurred via the epidural route. Cefazolin (six) and gentamicin (five) were the most common among 13 antibiotics involved. Intrathecal cephalosporin incidents (n = 6) were associated with devastating consequences (death, one, permanent residual neurological deficits, three). In the unsafe act category of the HFACS, the perceptual error contributing to occurrences of neuraxial antibiotics administration errors was due to IV-neuraxial device (e.g. intrathecal drain or catheter, epidural catheter) confusion (eight patients) or syringe/infusion bag swap (nine patients). Conclusions Intrathecal cephalosporins and gentamicin administration are associated with devastating consequences. Prevention of neuraxial antibiotic administration requires improvements in clinical deficiencies and the implementation of supporting technological tools to prepare and administer antibiotics correctly, thereby ensuring patient safety.